Des biens communs aux biens publics mondiaux - Bernard Hours (Développement Durable et Territoires)
The notion of common good has a specific role at the present time of globalisation. The concept of global public good is also used in this context. These terms, close together but also different, bring to the questions of appropriation, production and scarcity. This article first reminds the main anthropological approaches on circulation of goods, exchanges, and appropriation. The notion of common goods makes a reference to a golden age, a lost paradise before property. Then we propose a critical analysis of global public goods which are supposed to sublimate  global exploitation and competition.